The Franz Boas Papers, Volume 2 : Franz Boas, James Teit, and Early Twentieth-Century Salish Ethnography - Boas, Franz, 1858-1942; Darnell, Regna; American Philosophical Society; Project Muse. (Lincoln : University of Nebraska Press, 2015)
"This inaugural volume of The Franz Boas Papers Documentary Edition series presents current scholarship from the various academic disciplines that were shaped and continue to be influenced by Franz Boas (1858-1942). Few of Boas's intellectual progeny span the range of his disciplinary and public engagements. In his later career, Boas moved beyond Native American studies to become a public intellectual and advocate for social justice, particularly with reference to racism against African Americans and Jews and discrimination against women in science. He was a passionate defender of academic freedom, rigorous scholarship, and anthropology as a humane calling. The Franz Boas Papers, Volume 1 examines Boas's stature as a public intellectual in three crucial dimensions: theory, ethnography, and activism. The volume's contributors move across many of the disciplines within which Boas himself worked, bringing to bear their expertise in Native studies, anthropology, history, linguistics, folklore, ethnomusicology, museum studies, comparative literature, English, film studies, philosophy, and journalism. This volume demonstrates a contemporary urgency to reassessing Boas both within the field of anthropology and beyond."--
Volume 1. Historiographic conundra : the Boasian elephant in the middle of anthropology's room / Regna Darnell -- Mind, body, and the Native point of view : Boasian theory at the centennial of The mind of primitive man / Regna Darnell -- The individual and individuality in Franz Boas's anthropology and philosophy / Herbert S. Lewis -- The police dance : dissemination in Boas's field notes and diaries, 1886-1894 / Christopher Bracken -- Franz Boas and the conditions of literature / J. Edward Chamberlin -- From Baffin Island to Boasian induction : how anthropology and linguistics got into their interlinear groove / Michael Silverstein -- The Boasian legacy in ethnomusicology : cultural relativism, narrative texts, linguistic structures, and the role of comparison / Sean O'Neill -- Friends in this world : the relationship of George Hunt and Franz Boas / Isaiah Lorado Wilner -- The ethnographic legacy of Franz Boas and James Teit : The Thompson Indians of British Columbia / Andrea Laforet -- Anthropological activism and Boas's Pacific Northwest ethnology / David W. Dinwoodie -- Franz Boas, Wilson Duff, and the image of anthropology in British Columbia / Robert L.A. Hancock -- Cultural persistence in the age of "hopelessness" : Phinney, Boas, and U.S. Indian policy / Joshua Smith -- Franz Boas's correspondence with German friends and colleagues in the early 1930s / Jürgen Langenkämper -- Franz Boas on war and empire : the making of a public intellectual / Julia E. Liss -- Anthropology of revitalization : digitizing the American Philosophical Society's Native American collections / Timothy B. Powell -- "An expansive archive ... not a diminished one" : The Franz Boas Papers Documentary Edition Project / Michelle Hamilton.
Volume 1 is the product of a conference held in December 2010 at the University of Western Ontario.
"In partnership with the American Philosophical Society (APS) and the University of Nebraska Press, this volume initiates an ambitious project to digitize and critically edit the Franz Boas papers. We anticipate approximately twenty-five volumes ..."--Volume 1, page 345.
Volume 1. Franz Boas as public intellectual : theory, ethnography, activism / edited by Regna Darnell, Michelle Hamilton, Robert L.A. Hancock, and Joshua Smith.
Description based on print version record.
JSTOR
Keywords: Boas, Franz, -- 1858-1942 -- Influence; Boas, Franz, -- 1858-1942 -- Notebooks, sketchbooks, etc; Boas, Franz, -- 1858-1942 -- Diaries; Boas, Franz, -- 1858-1942 -- Correspondence; Boas, Franz, -- 1858-1942; Boas, Franz -- 1858-1942; Ethnology -- North America -- History; Ethnologie -- Amérique du Nord -- Histoire; SOCIAL SCIENCE -- Anthropology -- General; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; BIOGRAPHY & AUTOBIOGRAPHY / Historical; Influence (Literary, artistic, etc.); Ethnology; North America; Wissenschaft; Rezeption; Theorie; Aktivismus; Ethnologie; Personal correspondence; Notebooks, sketchbooks, etc; History; Diaries